2016
DOI: 10.1161/atvbaha.116.308335
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Cells Require CD98 for Efficient Angiogenesis—Brief Report

Abstract: Objective CD98 regulates integrin signaling and is critical for tumor cell proliferation. It is also expressed on endothelial cells (EC) but its role in angiogenesis is unclear. Approach and Results We used specific genetic targeting and antibody blockade approaches to examine the function of CD98 in EC proliferation, blood vessel growth, and tumor angiogenesis. It is up-regulated on angiogenic endothelial cells and EC-specific deletion of CD98 in mice inhibited tumor growth, retinal angiogenesis, and EC pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…In this regard, it has been shown that over-expression of SLC3A2 is actively involved in the proliferation of vascular smooth muscle cells and is necessary for efficient angiogenesis. 38, 39 In this study, ER+ high-proliferation and TN tumours showed the most significant positive correlation between the mRNA expression of SLC3A2 and vascular endothelial growth factor B, which maintains the continuity of angiogenesis and thus implicated for the metastatic process. 40 Although the association between HER2+ tumours and patient outcome was not nominally significant, there was no difference in the effect of this subtype and the other aggressive tumour types.…”
Section: Discussionmentioning
confidence: 50%
“…In this regard, it has been shown that over-expression of SLC3A2 is actively involved in the proliferation of vascular smooth muscle cells and is necessary for efficient angiogenesis. 38, 39 In this study, ER+ high-proliferation and TN tumours showed the most significant positive correlation between the mRNA expression of SLC3A2 and vascular endothelial growth factor B, which maintains the continuity of angiogenesis and thus implicated for the metastatic process. 40 Although the association between HER2+ tumours and patient outcome was not nominally significant, there was no difference in the effect of this subtype and the other aggressive tumour types.…”
Section: Discussionmentioning
confidence: 50%
“…Focused study of the mechanisms of vascular development can produce surprising clues about adult vascular disease as cells respond to tissue damage and reexpress developmental programs to repair injury and remodel vessel walls. 101106…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, CD98 expression is implicated in increased vascular density (Supplemental Figs. 2A and 2B, bottom) (26). The correlation between vascular density and LAT1 expression is corroborated by preclinical 11 C-methionine PET studies on gliomas and brain tumors (27 Data are mean correlation coefficient followed by 5%-95% confidence interval in parentheses.…”
Section: Discussionmentioning
confidence: 77%